2015
DOI: 10.1007/s11269-015-0995-x
|View full text |Cite
|
Sign up to set email alerts
|

Towards Adaptation to Climate Change: Water for Rice in the Coastal Wetlands of Doñana, Southern Spain

Abstract: Rice production in coastal wetlands provides critical ecosystem services that range from flood control to wildlife habitat. In the Iberian Peninsula rice was introduced in the 10th Century. Today Iberian rice accounts for about one quarter of the total rice production of the European Union, almost exclusively cultivated in the coastal wetlands of Spain, with permanent flooding. The intensive water management required to produce rice stands at a crucial point since freshwater supply is deteriorating at an unpre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
15
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 37 publications
(32 reference statements)
0
15
0
Order By: Relevance
“…According to McMichael et al [3], agriculture has depleted natural resources, contributing to water scarcity. To face this problem, strategies have been proposed such as increasing water use efficiency [4], desalination [5,6], water transactions [7,8], use of infrastructure for water storage [9,10], and optimisation of resources [11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…According to McMichael et al [3], agriculture has depleted natural resources, contributing to water scarcity. To face this problem, strategies have been proposed such as increasing water use efficiency [4], desalination [5,6], water transactions [7,8], use of infrastructure for water storage [9,10], and optimisation of resources [11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…make and how they use information to support those decisions, and decision modelling to explore how additional information can be used to inform and influence the decision process. As stated by Iglesias et al (2017), the main advantage of the semi structured interviews method is these encourage discussion, while the main limitations are related to the small sample size which means that only a partial view is obtained of the plurality of the stakeholders that make these decisions. Despite the limitations, the responses of the interviews provided a detailed description of the possible choices to deal with water shortages 5 in the Ebro basin, and the interaction and feedbacks between water management strategies at basin, irrigation district and local farmer scales by providing increased comprehension of the stakeholders' views.…”
mentioning
confidence: 99%
“…These papers are functional in -representing and demonstrating a wide range of tools to assess risk of fresh water shortage under climate change at both local (Stofberg et al, 2016) and regional scale (Stigter et al, 2015, Giannikopouloua et al, 2015, and Iglesias et al, 2015, -providing practical examples of how to systematically compare different adaptation strategies (Giannikopouloua et al 2015) and socio-economic development scenarios (Stigter et al, 2015). -exploring novel methods to develop resilient, robust and flexible adaptation plans (Thissen et al, 2015) to account for a range of future developments (Stigter et al, 2015) -and showing that adoption of new technologies such as presented by Zuurbier et al, 2016 and inventoried by Iglesias et al.…”
mentioning
confidence: 99%
“…-exploring novel methods to develop resilient, robust and flexible adaptation plans (Thissen et al, 2015) to account for a range of future developments (Stigter et al, 2015) -and showing that adoption of new technologies such as presented by Zuurbier et al, 2016 and inventoried by Iglesias et al. Iglesias et al, 2015 depend mostly on the risk perception and the confidence in these technologies (Veraart et al, 2016), which in turn is influenced by demonstrated success in terms of reliability and the costs-benefits ratio (Veraart et al, 2016and Zuurbier et al, 2016) Veraart et al (2016 evaluate the socio-economic factors that determine the wider use of adaptation measures at farm level in a few pilot studies in the Southwestern part of the Netherlands.…”
mentioning
confidence: 99%
See 1 more Smart Citation